Peningkatan Pelayanan Sarana dan Prasarana Balai Benih Ikan di Kabupaten Pinrang - Zaki Muhammad; Muhammad Yusri Lukman; Adithya Yudistira (Universitas Muslim Indonesia, 2021)
BBI is one of the government-owned facilities that has a function to provide fish seeds, be it consumption fish or ornamental fish needed by grow-out fish farmers. Freshwater Fish Seed Center (BBI) Malimpung, Pinrang Regency, is a central unit that was established as an alternative in efforts to develop natural resources, especially in the field of fisheries to meet the need for quality freshwater fish seeds. The purpose of this activity is to plan and redesign the master plan for the development of the Pinrang Regency Fish Seed Center by taking into account the problems and potentials in the planning area, and their impact on the surrounding environment. The methods used in carrying out this activity are 1) Determination of territorial boundaries including administrative boundaries of the planning area, 2) Field observations (site observation) especially carried out on visits to planning locations that have the potential to be developed as Fish Seed Centers (BBI), 3) The identification of the results of the inventory of the planning area is accompanied by a map of the area. The above conditions are not visually good where the standards set by the government in this case the Ministry of Maritime Affairs and Fisheries are strongly recommended that each aquaculture area must have a representative area marker in the form of an area gate and other markers. and also environment must have a barrier between the environmental road and the cultivation area, the barrier can be a Living Fence Vegetation, or a Massive Fence.